ANALYSIS ON CALCULATION METHOD OF RISER IN SHELL AND TUBE WASTE HEAT BOILER - HU Tao; ZHANG Fan (Jixie qiangdu)
Water recycle system is formed by shell and tube waste heat boiler body,drum,down comer and riser. The riser connects boiler body and drum. When the production of steam is less account in the system,the riser supports the whole mass of boiler drum and bears internal pressure,boiler drum’s operating mass,seismic load and wind load. In this paper,FEA of riser was completed by ANSYS,and the local stresses on the shell were studied with the change of different thicknesses of riser. Thus,the thickness of riser was confirmed to achieve material rationality and economical efficiency.